Case–case analysis of Campylobacter and Salmonella – using surveillance data for outbreak investigations and monitoring routine risk factors. Issue 15 (10th August 2018) - Pogreba-Brown, K.; O'Connor, P.; Matthews, J.; Barrett, E.; Bell, M. L.
Abstract: Utilising routine surveillance data, this study presents a method for generating a baseline comparison that can be used in future foodborne outbreak investigations following a case–case methodology. Salmonella and Campylobacter cases (2012–2015) from Maricopa County, AZ were compared to determine differences in risk factors, symptoms and demographics. For foods and other risk factors, adjusted odds ratios were developed using Campylobacter as the reference. Comparisons were also made for three major Salmonella subtypes, Typhimurium, Enteritidis and Poona as compared with Campylobacter . Salmonella cases were younger, while Campylobacter cases were more Hispanic and female. Campylobacter cases reported consuming peppers, sprouts, poultry, queso fresco, eggs and raw nuts more and reported contact with animal products, birds, visiting a farm or dairy, owning a pet, a sick pet, swimming in a river, lake or pond, or handling multiple raw meats more. Salmonella cases reported visiting a petting zoo and contact with a reptile more. There were significant variations by Salmonella subtype in both foods and exposures. We recommend departments conduct this analysis to generate a baseline comparison and a running average of relevant odds ratios allowing staff to focus on trace-back of contaminated food items earlier in the outbreak investigation process.